The Bongal Site in the Dynamics of Indian Ocean Maritime Trade Networks, 7th–11th Centuries - Thania Paskah Margaretha Sinaga; Adilla Aura Putri; Yunita Pebrina; Alya Nataly; Muhammad Fahrijal Tanjung (Local History & Heritage, 2026)
This study examines archaeological findings from the Bongal Site, Central Tapanuli Regency, to understand its role in the Indian Ocean maritime network between the 7th and 11th centuries. Using a qualitative historical-archaeological approach supported by artifact analysis and literature review, the study addresses how material evidence reflects early transregional interactions. Archaeological discoveries at the Bongal Site indicate that the west coast of Sumatra functioned as an international maritime hub, as evidenced by artifacts such as a Nestorian Christian hand cross, Abbasid silver coins, Tang Dynasty coins, and Persian glass fragments. These findings reflect extensive trade networks linking the Islamic world, East Asia, Persia, and the Indonesian archipelago. The Nestorian cross provides early evidence of Eastern Christianity prior to European colonial expansion, while Abbasid coins demonstrate economic integration with the Islamic world since the 8th century. Tang coins indicate active trade relations with China, and Persian glass suggests the exchange of luxury goods and Middle Eastern merchant involvement in camphor trade. Collectively, these findings position Bongal as a cosmopolitan port and contribute to maritime historiography and early religious diffusion studies in Southeast Asia.